ANALISIS PELAPORAN NILAI KRITIS HASIL PEMERIKSAAN LABORATORIUM DI RUMAH SAKIT MAYJEND HM RYACUDU KABUPATEN LAMPUNG UTARA - Hidayat, Rahmat; Kurniawan, Entuy; Rahayu, Ira Gustira; Wiryanti, Wiwin (UI Scholars Hub, 2024)
Critical values are abnormal values indicating high-risk/pathophysiological conditions that threaten the patient's life and require immediate medical intervention. Reporting critical laboratory values must be done quickly and accurately to the patient's responsible physician (DPJP) to ensure prompt and appropriate treatment. The aim of this study is to understand the reporting of critical laboratory values and its impact on the clinical decisions of doctors. This research uses both quantitative and qualitative methods with a descriptive analysis approach. Data collection was conducted through in-depth interviews, documentation, and observation. Informants were 15 DPJP. The results of this study show that the reporting system for critical laboratory values is functioning well/appropriately, with an average reporting time of 14.6 minutes, the fastest being 9 minutes, and the longest being 22 minutes. However, some DPJPs desire faster reporting times because the current system still uses manual methods, such as mobile phone calls or direct delivery of critical lab results to the ward by staff. Consequently, if there are disruptions in mobile phone service or a shortage of staff, it can take longer. Meanwhile, the timeliness of reporting and the accuracy of critical laboratory values in relation to the doctor's clinical decisions have been satisfactory/appropriate.